Analisis Kebijakan Retribusi Pelayanan Persampahan di Dinas Lingkungan Hidup Kabupaten Gorontalo - Kumali, Ayunda Nursyahbani Putri; Sulila, Ismet; Isa, Rusli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research discusses the implementation of waste service retribution policy in the Environmental Agency of Gorontalo Regency. The purpose of this research is to analyze how the implementation of waste service retribution policy in Gorontalo District Environmental Agency. This research uses a descriptive qualitative approach. Data were collected through interviews, observation, and documentation. The results showed that the implementation of retribution policy is still not optimal. Factors that support the implementation of waste service levy policy in Gorontalo District Environmental Agency are clear communication transmission, competent human resources, professional attitude of implementers and clear Standard Operating Procedure (SOP), good inter-agency coordination mechanism. Meanwhile, factors that hinder the implementation of waste service levy policy in Gorontalo District Environmental Agency are lack of communication and consistency of communication between policy makers and the community, limited human resources, non-human resources and financial resources, lack of officer response to community complaints, and weak monitoring and evaluation system. Therefore, through the findings of this study, the researcher concludes that there is a need to increase the effectiveness of the waste service retribution policy, which requires a better communication strategy, increasing the number and capacity of retribution officers, increasing the number of supporting facilities, increasing operational costs, and improved monitoring and evaluation mechanisms